Ethnic Disparities in Dental Caries among Adolescents in China. (May 2021) - Wu, S.C.; Ma, X.X.; Zhang, Z.Y.; Lo, E.C.M.; Wang, X.; Wang, B.; Tai, B.J.; Hu, D.Y.; Lin, H.C.; Wang, C.X.; Liu, X.N.; Rong, W.S.; et al.
Comprehensive research on ethnic disparities in dental caries in China is limited. The aims of this cross-sectional study were to compare the levels of dental caries in adolescents between the Han ethnic group and ethnic minority groups in China and to explore the risk indicators for dental caries within ethnic subgroups. Data from the Fourth National Oral Health Survey in 2015, which covered all 31 province-level administrative divisions in mainland China, were used. The dental caries status in the permanent dentition of adolescents aged 12, 13, 14, and 15 y was measured using the decayed, missing, and filled teeth (DFMT) score, and sociodemographic characteristics and oral health–related behaviors were also collected. A total of 118, 601 adolescents were included, with ethnic minority groups accounting for 13.15%. Of the Han and minority groups, the standardized prevalence of dental caries experience was 40.58% and 47.67%, and the mean DMFT scores were 0.97 and 1.28, respectively. According to the multivariate zero-inflated negative binomial regression analysis, the caries status of minorities was more severe than Han adolescents (adjusted prevalence rate ratio [PRR], 1.14; 95% confidence interval [CI], 1.10–1.18). This disparity was greater among adolescents who lived in rural areas, had mid-level economic status, and frequently consumed sugary beverages. After propensity score matchings, Uygur (PRR, 1.44; 95% CI, 1.25–1.67), Tibetan (PRR, 1.39; 95% CI, 1.3–1.48), and Yi (PRR, 1.24; 95% CI, 1.04–1.48) adolescents were significantly more likely to have caries than Han adolescents. Subgroup analyses revealed that gender, age, location of residence, economic status, region, consumption of sweet snacks and sugary beverages, and dental visit pattern were significantly associated with dental caries within ethnic minorities.